Exposition of the Apocalypse - Ticonius, active 4th century (Book collections on Project MUSE., 2017)
The Exposition of the Apocalypse by Tyconius of Carthage (fl. 380) was pivotal in the history of interpretation of the Book of Revelation. Tyconius interpreted John's visions as figurative of the struggles facing the Church throughout the entire period between the Incarnation and the Second Coming of Christ.